PENGARUH CITRA MEREK, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MASKARA MAYBELLINE - Serli Apriani; Khairul Bahrun (Yayasan Insani Mandiri Santani, 2021)
This study aims to determine the effect of Brand Image, Product Quality on Decision to Purchase Maybelline Mascara Cosmetics in Management Study Program Students, Faculty of Economics and Business at Muhammadiyah Bengkulu University. There are several factors that will be discussed in this study, including brand image, product quality and purchasing decisions. This research uses quantitative research methods. The population in this study were all students of the Management Study Program at the Faculty of Economics and Business at Muhammadiyah Bengkulu University who used Maybelline mascara cosmetics, with the sampling method using Simple Random Sampling method, in conducting the research the respondents were obtained random. In this study using data collection methods by means of observation, interviews and distributing questionnaires or questionnaires. The data that has been collected is then processed using test instruments, Analysis of Respondents' Responses, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination (R2) and also Hypothesis t and hypothesis f.Based on the results of multiple linear regression analysis, the formulation of Y = 3.630 + 0.314 (X1) + 0.290 (X2) is obtained. The determinant coefficient R2 = 0.572 or 57.2% while the remaining 0.428 or 42.8% is influenced by other variables not included in this research model. The results of the tests that have been carried out can be seen that the Brand Image variable (X1) shows t count of 2.721> t table 1.99601 with a significant level of 0.008 <0.050, the Product Quality variable (X_2) shows the tcount of 5.227> t table 1.99601 with a significant level of 0.000 <0.050. The results of the F test show that the significance value of F is 0.000 less than 0.050 and Fcount is greater than Ftable, 44.709> 3.133, from the results of data management it can be concluded that the brand image and product quality partially or simultaneously have a positive and significant effect on purchasing decisions.Keywords: Brand Image, Product Quality, and Purchase Decision